How to establish and run a cell therapy unit in a blood bank. (July 2013) - Gabriel, C.
<x xml:space="preserve">Abstract</x> Establishing a cell therapy unit in a blood bank is a new idea, which seemingly alleviates the current pressure to develop new therapies. However, the way Ahead is full of hurdles. Strategic planning is recommended and should be emphasized even more, as risks are high and cell therapies are costly. Especially, the mixture of staffing, designing facilities and organizational aspects are a burden. Executing the establishment in a step‐by‐step approach makes the tasks easier and has a high possibility of success.